2013
DOI: 10.1095/biolreprod.113.107987
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evidence for Bone Marrow as a Source of Nonhematopoietic Endometrial Stromal and Epithelial Compartment Cells in a Murine Model1

Abstract: Human endometrium has the remarkable ability to regenerate all cellular compartments with every menstrual cycle; the cellular source remains unknown. The objective of the present study was to determine whether the bone marrow (BM) is a source of multiple endometrial cell types using a murine BM transplant model. BM cells were harvested from transgenic donor mice that ubiquitously express green fluorescent protein (GFP) and were injected into lethally irradiated, syngeneic female recipient mice. Recipients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 18 publications
4
41
1
3
Order By: Relevance
“…GFP reporters driven by the mTert and Ch β ‐actin promoters identified CD45 + bone marrow‐derived immune cells in the endometrium, but provided no evidence for a bone marrow‐derived, CD45 – non‐hematopoietic lineage contribution to the endometrium. This conclusion is in contrast to previous studies reporting the existence of non‐leukocyte bone marrow‐derived endometrial cells .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…GFP reporters driven by the mTert and Ch β ‐actin promoters identified CD45 + bone marrow‐derived immune cells in the endometrium, but provided no evidence for a bone marrow‐derived, CD45 – non‐hematopoietic lineage contribution to the endometrium. This conclusion is in contrast to previous studies reporting the existence of non‐leukocyte bone marrow‐derived endometrial cells .…”
Section: Discussioncontrasting
confidence: 99%
“…Hematopoietic reconstitution with traceable bone marrow (using transgenic, sex‐mismatched, or HLA‐mismatched cells) has been widely used to identify the products of HSC transdifferentiation in various tissues including endometrium . While one of these studies also used mice expressing CD45 ‐Cre combined with a Cre‐activated GFP reporter to trace CD45 + bone marrow cells , the bulk of evidence for bone marrow‐derived endometrial cells originates from studies employing bone marrow transplantation.…”
Section: Discussionmentioning
confidence: 99%
“…We also detected a robust increase in expression of Snai3 (5 fold at 8 hours, 15 fold at 24 hours). Mice with knockout of Snai3 are viable and fertile but double knockout of Snai2/3 resulted in marked depletion of bone-marrow derived cells [38] raising the possibility that Snai3 may play a previously unrecognised role in regulation of bone-marrow derived cells in the uterus [39]. We also speculate that reduced expression of Snai2 (Slug) at 8 and 12 hours might relieve repression of the Cdh1 gene favouring epithelial cell fate.…”
Section: Discussionmentioning
confidence: 88%
“…However, we cannot exclude the possibility that the epithelial BrdU + cells may originate from a circulating source such as the bone marrow. Morelli et al [66] showed bone marrow cells can serve as a cellular source for cyclic replenishment of multiple endometrial cell types. Bone marrow-derived stem cells can transdifferentiate into endometrial epithelial and stromal cells [67].…”
Section: Environmental Niches and Lrscmentioning
confidence: 99%